2011
DOI: 10.3762/bjoc.7.62
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic evaluation of the solvolysis of isobutyl chloro- and chlorothioformate esters

Abstract: SummaryThe specific rates of solvolysis of isobutyl chloroformate (1) are reported at 40.0 °C and those for isobutyl chlorothioformate (2) are reported at 25.0 °C, in a variety of pure and binary aqueous organic mixtures with wide ranging nucleophilicity and ionizing power. For 1, we also report the first-order rate constants determined at different temperatures in pure ethanol (EtOH), methanol (MeOH), 80% EtOH, and in both 97% and 70% 2,2,2-trifluoroethanol (TFE). The enthalpy (ΔH≠) and entropy (ΔS≠) of activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 59 publications
3
24
1
Order By: Relevance
“…Similarly, the primary isobutyl chlorothioformate also reacts primarily by the ionization pathway [46], with evidence for a dominant A-E pathway only in 100% and 90% ethanol, 100% and 90% methanol, and 20% TFE-80% ethanol.…”
Section: Chlorothioformatesmentioning
confidence: 99%
“…Similarly, the primary isobutyl chlorothioformate also reacts primarily by the ionization pathway [46], with evidence for a dominant A-E pathway only in 100% and 90% ethanol, 100% and 90% methanol, and 20% TFE-80% ethanol.…”
Section: Chlorothioformatesmentioning
confidence: 99%
“…In the present study we consider the solvolyses of a tertiary alkyl chlorothioformate ( t -BuSCOCl, 1 ). It has previously been shown [59] for chloroformates that the replacement of the alkoxy oxygen by sulfur leads to a move away from an addition-elimination mechanism (Scheme 1) towards one of several possible ionization mechanisms (Scheme 2). …”
Section: Introductionmentioning
confidence: 99%
“…The solvent systems divided into 100%TFE, 97%TFE, 97, 90, 70, 50%HFIP (n = 6) and the remainder (n = 22), from ref. [13]. h From ref.…”
Section: Values Of Enthalpy (δHmentioning
confidence: 99%
“…(1) and (2), we previously reported that the results of primary, secondary and tertiary alkyl chloroformates (ROCOCl) in a wide range of solvent mixtures can follow bimolecular and/or unimolecular pathways. [10][11][12][13][14][15][16][17] Kevill and D'Souza 10 showed that, particularly in ethyl chloroformate (4,EtOCOCl) solvolysis, an addition-elimination mechanism dominates [l = 1.56, m = 0.55] in all except the highly ionizing solvents, and the major reaction channel in the least nucleophilic solvents involves ionization mechanism [l = 0.69, m = 0.82]. Bentley et al also carried out a series studies of the solvolyses of acyl chloride and their derivatives using the G-W equation.…”
mentioning
confidence: 99%